The Excited-State Creutz–Taube Ion - Pieslinger, German E.; Ramírez-Wierzbicki, Ivana; Cadranel, Alejandro (Angewandte Chemie International Edition, 2022)
The excited-state version of the Creutz–Taube ion was prepared via visible light excitation of [(NH3)5RuII(μ-pz)RuII(NH3)5]4+. The resulting excited state is a mixed valence RuIII–δ(μ-pz⋅−)RuII+δ transient species, which was characterized using femtosecond transient absorption spectroscopy with vis-NIR detection. Very intense photoinduced intervalence charge transfers were observed at 7500 cm−1, revealing an excited-state electronic coupling element HDA=3750 cm−1. DFT calculations confirm a strongly delocalized excited state. A notable consequence of strong electron delocalization is the nanosecond excited state lifetime, which was exploited in a proof-of-concept intermolecular electron transfer. The excited-state Creutz–Taube ion is established as a reference, and demonstrates that electron delocalization in the excited state can be leveraged for artificial photosynthesis or other photocatalytic schemes based on electron transfer chemistry.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Electron Transfer; Electronic Coupling; Excited States; Intervalence; Mixed Valence